URGENSI PENERAPAN ASAS SINGLE PROSECUTION SYSTEM DALAM MEWUJUDKAN KEPASTIAN HUKUM - Mohammad Haikal Dzikrullah; Sri Wahyu Handayani; Abdul Aziz Nasihuddin (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: As a state governed by the rule of law, Indonesia establishes law as the primary foundation for achieving legal certainty (*rechtszekerheid*) within the criminal justice system. However, the post-reform era has witnessed a fragmentation of prosecutorial authority resulting from the enactment of various special laws (*lex specialis*) outside the codified Criminal Procedure Code (KUHAP). Prosecutorial authority is now distributed among autonomous institutions such as the Attorney General's Office, the Corruption Eradication Commission (KPK), and the Military Prosecution Service (*Oditurat Militer*). This institutional fragmentation severs the single chain of command, fosters sectoral ego, and creates jurisdictional overlaps, particularly in cases involving joint military-civilian jurisdiction (*koneksitas*). This study aims to analyze the urgency of implementing a "Single Prosecution System" within Indonesia's criminal justice system as a means to address institutional fragmentation and achieve genuine legal certainty. The study employs a normative legal research method (*doctrinal legal research*) utilizing statutory, conceptual, and limited comparative approaches. Data collection relies on library research—encompassing primary and secondary legal sources—followed by qualitative analysis using deductive legal reasoning (syllogism). The findings indicate that the dualistic and trialistic nature of prosecution undermines the principles of substantive and procedural legal certainty and violates the principle of equality before the law. The absence of uniform national prosecution guidelines leads to sharp disparities in sentencing demands and eliminates the predictability of verdicts. Furthermore, the lack of unification creates chronic procedural obstacles, such as the "ping-pong" effect of case files being repeatedly returned between agencies, thereby prolonging the detention of defendants. Consequently, there is an urgent need to revitalize the pure "Single Prosecution System" principle and strengthen the *dominus litis* doctrine. All prosecutorial functions within specialized institutions must be integrated under a unified authority, coordinated and supervised by the Attorney General as the state's highest public prosecutor. The establishment of the Junior Attorney General for Military Criminal Affairs (Jampidmil) should serve as a blueprint—with its scope expanded through revisions to the Criminal Procedure Code (KUHAP) and the Prosecution Service Law—to cut red tape, restore public trust, and ensure equal justice. Keywords: Single Prosecution System; Dominus Litis; Legal Certainty; Integrated Criminal Justice System; Prosecution Service   Abstrak: Indonesia sebagai negara hukum meletakkan hukum sebagai landasan utama guna mewujudkan kepastian hukum (rechtszekerheid) dalam sistem peradilan pidana. Namun, pasca-reformasi terjadi fragmentasi otoritas penuntutan akibat lahirnya berbagai undang-undang khusus (lex specialis) di luar kodifikasi KUHAP. Kewenangan penuntutan kini terbagi secara atributif kepada lembaga-lembaga otonom seperti Kejaksaan Agung, Komisi Pemberantasan Korupsi (KPK), dan Oditurat Militer. Fragmentasi kelembagaan ini memutus rantai komando penuntutan tunggal (single command), memicu ego sektoral, dan menimbulkan tumpang tindih yurisdiksi, terutama dalam perkara koneksitas. Penelitian ini bertujuan untuk menganalisis urgensi penerapan asas Single Prosecution System (sistem penuntutan tunggal) dalam sistem peradilan pidana Indonesia sebagai upaya mengatasi fragmentasi kelembagaan dan mewujudkan kepastian hukum yang hakiki. Penelitian ini menggunakan metode penelitian hukum normatif (doctrinal legal research) dengan pendekatan perundang-undangan (statute approach), pendekatan konseptual (conceptual approach), dan pendekatan perbandingan (comparative approach) secara terbatas. Sumber data bertumpu pada studi kepustakaan (library research) yang meliputi bahan hukum primer dan sekunder, yang kemudian dianalisis secara kualitatif dengan penalaran hukum berbasis logika deduktif (silogisme). Hasil penelitian menunjukkan bahwa dualisme dan trialisme penuntutan berimplikasi pada degradasi asas kepastian hukum substantif maupun prosedural, serta mencederai asas kesamaan di hadapan hukum (equality before the law). Ketiadaan standar pedoman penuntutan nasional yang seragam memicu disparitas tuntutan yang tajam dan menghilangkan aspek prediktabilitas putusan. Selain itu, ketiadaan unifikasi menimbulkan hambatan prosedural kronis, seperti fenomena bolak-balik berkas perkara yang memperpanjang masa penahanan terdakwa. Oleh karena itu, reaktualisasi asas single prosecution system yang murni dan penguatan doktrin dominus litis mendesak untuk diimplementasikan. Seluruh fungsi penuntutan pada lembaga khusus harus diintegrasikan di bawah satu pintu, koordinasi, dan supervisi Jaksa Agung selaku penuntut umum tertinggi negara. Pembentukan Jaksa Agung Muda Bidang Pidana Militer (Jampidmil) harus dijadikan cetak biru (blueprint) yang diperluas jangkauannya melalui pembaruan RUU KUHAP dan UU Kejaksaan demi memotong birokrasi, memulihkan kepercayaan publik (public trust), serta menjamin keadilan yang setara. Kata Kunci: Single Prosecution System; Dominus Litis; Kepastian Hukum; Peradilan Pidana Terpadu; Kejaksaan